The influence of online distance learning and digital skills on digital literacy among university students post Covid-19 - Arandas, Mohammed Fadel; Salman, Ali; Syed Abdullah Idid, Syed Arabi; Loh, Yoke Ling; Nazir, Syaira; Ker, Yuek Li (National Association for Media Literacy Education, 2024)
Online distance learning policies were formulated and implemented among some Malaysian universities long ago, but their value emerged since COVID-19. Emanating from the diffusion of innovation theory, this study examined the perception of higher education students on the influence and relationship between six independent variables (compatibility, observability, relative advantage, complexity, trialability, and digital skills) and one dependent variable (digital literacy). A total of 524 respondents were sampled, comprising students from six public and private Malaysian universities. The findings from the correlation analysis show a significant positive relationship between the six independent variables and the dependent variable. Meanwhile, in the regression analysis, three of the independent variables (observability, trialability, and digital skill) have a significant and positive effect on digital literacy. This study placed the diffusion of innovation in a specific context that supports designing online distance learning and digital literacy policies.